Association between lipid accumulation product and chronic obstructive pulmonary disease: a cross-sectional analysis - Shaofeng Zhang; Zhongli Li; Yaling Zeng; Jia Jiang; Wei lei; Siqin Chen; Jiayi Liu; Jia Li; Xin Chen; Qiang Xiao (BMC Pulmonary Medicine)
Abstract Background Research indicates that obesity can worsen the clinical manifestations of chronic obstructive pulmonary disease (COPD). Timely detection of COPD has the potential to enhance treatment results. This study seeks to investigate the association between a new metabolic indicator, the lipid accumulation product (LAP), and the risk of developing COPD. Methods The observational analysis employs data from the National Health and Nutrition Examination Survey (NHANES) conducted from 2007 to 2016. Multivariate logistic regression was used to explore the association between LAP levels and COPD. Further analysis methods included subgroup analysis, smooth curve modeling, and threshold effect evaluation. Results Within the sample of 12,089 individuals, 1,072 were diagnosed with COPD. A positive correlation between LAP levels and COPD risk was identified through logistic regression analysis, even after controlling for potential confounders. The analyses by subgroup showed an enhanced association in participants without hypertension. The smooth curve fitting analysis highlighted particular saturation effects of LAP, with significant inflection points identified at 65.5278 and a P-value of 0.013. Conclusion This study's findings suggest that elevated LAP levels are associated with an increased risk of COPD. It is suggested that dietary modifications and exercise routines be implemented to mitigate COPD risk in those with higher LAP levels.